It takes two to tango: the interplay between decision logics, communication strategies and social media engagement in start-ups - Christian Rudeloff; Stefanie Pakura; Fabian Eggers; Thomas Niemand (Review of Managerial Science, 2021)
This manuscript analyzes start-ups' usage of different communication strategies (information, response, involvement), their underlying decision logics (effectuation, causation, strategy absence) and respective social media success. A multitude of studies have been published on the decision logics of entrepreneurs as well as on different communication strategies. Decision logics and according strategies and actions are closely connected. Still, research on the interplay between the two areas is largely missing. This applies in particular to the effect of different decision logics and communication models on social media success. Through a combination of case studies with fuzzy-set Qualitative Comparative Analysis this exploratory study demonstrates that different combinations of causal and absence of strategy decision logics can be equally successful when it comes to social media engagement, whereas effectuation is detrimental for success. Furthermore, we find that two-way-communication is essential to create engagement, while information strategy alone cannot lead to social media success. This study provides new insights into the role of decision logics and connects effectuation theory with the communication literature, a field that has been dominated by causal approaches.
Keywords: 650; Effectuation; Causation; Absence of strategy; Strategic communication; Communication management; Social media; Start-ups